Comparison of Wheat Flour and Tapioca Flour Towards Characteristics of White Oyster Mushroom Chips - Luh Suriati; Nyoman Rudianta (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2021)
White oyster mushroom chips are products that are in great demand today. In addition to delicious taste, it also contains nutrients that are beneficial for health. The quality of the chips is largely determined by the addition of the type and amount of flour added. The purpose of this study was to determine the effect of the ratio of wheat flour and tapioca flour on the characteristics of white oyster mushroom chips. This study used a completely randomized design with three replications. The treatments tested were the ratio of wheat flour and tapioca flour with levels: (90:10) %, (80:20) %, (70:30) %, (60:40) %, (50:50) %. Comparison of wheat flour and tapioca flour only had a significant effect on the subjective test of water content and carbohydrate content of white oyster mushroom chips. The objective test had a significant effect on the taste, texture, and overall acceptance of white oyster mushroom chips. Comparison of flour and tapioca flour 60: 40% produces white oyster mushroom chips with the best organoleptic score.